Managerial Ownership as a Governance Signal: Moderating the Effects of CSR, Tax Planning, and Intellectual Capital on Earnings Management - Petty Aprilia Sari; Petty Aprilia Sari; Tubagus Ismail; Munawar Muchlish; Agus Sholikhan Yulianto (IAEI, 2025)
This study aims to examine the impact of tax planning, intellectual capital and CSR on earnings management. As a research sample, 20 companies from 125 companies in the consumer goods industry sector listed on the Indonesian Stock Exchange were used. Data comes from annual reports released between 2021 and 2023. Multiple regression analysis was used to create a regression model for this study. The results of the study indicate that CSR affects earnings management, while Tax Planning and Intellectual Capital do not affect earnings management. Managerial Ownership can moderate the effect of CSR on earnings management, where Managerial Ownership cannot moderate effect of Tax Planning and Intellectual Capital earnings management. Re-research on earnings management is important as the practice can affect corporate transparency and accountability and impact investment and financial decisions. Research is needed to understand factors that influence earnings management and devise strategies that can prevent the harmful practice.